Engineering the comfort parameters of 100% cotton plain woven fabrics. Issue 9 (2nd September 2022) - Abel, Patricia Julie; Unmar, Roshan; Rosunee, Satyadev
Abstract: The comfort property of fabrics is becoming increasingly important as customers desire heat and moisture management-enabled clothing that match their physical activity levels and environmental factors. So far, little work has been reported with the objective of engineering comfort in fabrics and exploring the potential of 'engineered comfort' for value-addition. To develop textiles that meet this objective, predictive models of thermal absorptivity, thermal resistance, water-vapour resistance and air permeability of 100% cotton single-layer plain woven fabric were developed in this work, respectively. The effects of the fabric structural parameters, namely, the open area, relative contact area between the fabric and the skin, the areal density and thickness on the comfort parameters were studied. All the predictive models developed were implemented into a computer program on Visual C++. The software is expected to be implemented as a tool that will enable textile technologists to determine the optimum fabric construction parameters for different permutations of thermo-physiological comfort parameters and thermal contact feelings; for instance, high thermal insulation coupled with cool contact feeling or high water-vapour permeability with warm thermal contact effect. The yarn sett and yarn linear density of a given plain woven fabric are the only inputs required for running the ready-to-implement program. The output of the program was validated by comparing with experimental data generated on Alambeta, Permetest and FX 3300 air permeability tester equipment, respectively. Most of the fabric samples generated values of Thermal Absorptivity, Thermal Resistance and Water-Vapour Resistance with acceptable relative errors of less than 25%. In addition, the program reasonably predicted the trend in changes in Air Permeability with changes in fabric construction.